ELEMENTS OF CULTURE IN NOVEL TAPAK JEJAK BY FIERSA BESARI - Purwanto, Joko; Aini, Aisyah Nurul (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2022)
This research is motivated by the waning culture that exists in the community. Based on these problems, the purpose of this study is to describe the cultural elements of the people of Eastern Indonesia, precisely in the Papua region in the novel Tapak Jejak by Fiersa Besari. The method in this research is descriptive and qualitative. Data collection techniques in this study are listening techniques and note-taking techniques. The results of the analysis obtained cultural elements including (a) the language system includes: Papuan language and food names; (b) knowledge systems include: medical knowledge and natural knowledge; (c) the social system includes: helping, friendly, and socially caring.